Ekonomiczne i etyczne cele ziemiańskiego stronnictwa ,,klemensowczyków” w latach czterdziestych XIX wieku - Szymański, Zdzisław (Annales. Etyka w Życiu Gospodarczym, 2015)
The 1840s brought a certain revival both in intellectual life and efforts to modernizeagriculture in the Kingdom of Poland. Count Andrzej Zamoyski (1800–1874)played an inspiring role here. In all his properties replaced feudal service by rents.Moreover, even though the villein system was still in place, he was a spokesman fora transition to this more modern form of managing for the totality of the landedgentry. On his initiative, the periodical “Roczniki Gospodarstwa Krajowego”(“Polish Farming Annual”) came out. “Roczniki” brought in representatives of theKingdom’s landed gentry supporting actions aimed at economic development andthe promotion of civilization, soon to be called organic work.Representatives of the landowning party supporting the idea of organic workwere popularly called “klemensowczycy”, because of their participation in conventionsheld in Andrzej Zamoyski’s estate in the village of Klemensów. The leader ofthe “klemensowczycy” blazed a trail for Poland’s progress of civilization, where hewas characterized by Occidentalism, understood as referring to historical experiencesof the Western world.